MONITORING OF LAND USE CHANGES USING AERIAL PHOTOGRAPH AND IKONOS IMAGE IN BEDUGUL, BALI - I Wayan Sandi Adnyana; Fumihiko Nishio; Josaphat Tetuko Sri Sumantyo; Gede Hendrawan (National Institute of Aeronautics and Space of Indonesia (LAPAN), 2006)
There was change of expending land use in Bedugul. It is necessary to monito the change of highland of Bali, catchments area of Beratan, Buyan and Tamblingan lakes. In order to control land use change and to anticipate degradation of hydrology function of this area. This study is to monitor the land use change by remote sensing and GIS technique. To evaluate land use and land cover, aerial photograph imagery and Ikonos imagery were used. Over 22 years of observation (1981-2003), there was land use changes in the catchments area of Beratan, Buyan and Tamblingan lakes at Bedugul area. The area of settlement increased by 62.6 ha, dry land vegetable crops and forest decreased by 116.5 ha and 32.5 ha, respectively. The surface area of Buyan Lake was also decreased, due to sedimentation caused by erosion in the vegetables dry land crops. Planning the land use study on erosion and soil-water conservation in this area necessary, in order to control land use change, erosion, and sedimentation in the lakes. Keywords: land use, monitoring, aerial photograph, Ikonos image.